2017
DOI: 10.5751/es-09729-220413
|View full text |Cite
|
Sign up to set email alerts
|

Soil cultures – the adaptive cycle of agrarian soil use in Central Europe: an interdisciplinary study using soil scientific and archaeological research

Abstract: ABSTRACT. Today's global challenges (e.g., food security) are not unprecedented in human history. Starting with the Neolithic transition, the agricultural sector and society underwent several cultural and technological changes and endured natural challenges. These challenges and changes are analyzed by using the adaptive cycle metaphor and the social-ecological system as tools to show the complexity of human-environment interactions and their development. The analysis relies on archaeological, pedological, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 108 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…Moreover, it is acknowledged that even regional land degradation has global consequences (Conacher & Conacher, 1995; Leal Pacheco, Sanches Fernandes, Valle Junior, Valera, & Tarlé Pissarra, 2018). Soil erosion is an old phenomenon and the most important land degradation processes (Orr et al, 2017), which has been accompanying human landuse and land management through millennia (Dotterweich, 2008; Hoffmann et al, 2010; Smetanová, Verstraeten, Notebaert, Dotterweich, & Létal, 2017; Teuber et al, 2017).…”
Section: Soil Erosion Research In a Changing Worldmentioning
confidence: 99%
“…Moreover, it is acknowledged that even regional land degradation has global consequences (Conacher & Conacher, 1995; Leal Pacheco, Sanches Fernandes, Valle Junior, Valera, & Tarlé Pissarra, 2018). Soil erosion is an old phenomenon and the most important land degradation processes (Orr et al, 2017), which has been accompanying human landuse and land management through millennia (Dotterweich, 2008; Hoffmann et al, 2010; Smetanová, Verstraeten, Notebaert, Dotterweich, & Létal, 2017; Teuber et al, 2017).…”
Section: Soil Erosion Research In a Changing Worldmentioning
confidence: 99%
“…phase changes in the adaptive cycle at one scale, particularly to examine the overexploitation of natural resources (i.e., Walker et al 1981, Beier et al 2009, Soane et al 2012. A subset of studies have used similar historical narratives to explore ecological dynamics within food systems (Fraser 2003, Allison and Hobbs 2004, McAllister et al 2006, Fraser 2007, Dugmore et al 2009, Moen and Keskitalo 2010, Rosen and Rivera-Collazo 2012, Perez Rodriguez and Anderson 2013, Stroink and Nelson 2013, Salvia and Quaranta 2015, Rawluk and Curtis 2016, Teuber et al 2017, Jiménez et al 2020. These studies apply the adaptive cycle and/ or panarchy in one SES over time.…”
Section: Cross-scale Analyses Of Food Systemsmentioning
confidence: 99%
“…Sustainable agricultural methods consist of different microhabitats with excellent environmental fluctuations and genetic biodiversity [78]. Reports from agrarian soils confirmed that there are high microbial stock and plant development promotion pursuits [79]. Many studies are showing the latest metagenomic improvements in agriculture [76][77][78].…”
Section: Metagenomics For Sustainable Agricultural Practicesmentioning
confidence: 99%